How Do Comeback Korean Pop Performers Acquire Audience Empathetic Attachment and Sustained Loyalty? Parasocial Interactions Through Live Stream Shows - Ma, Zhuang; Song, Linpei; Zhou, Jue; Chong, Woonkian; Xiong, Wantong (Frontiers in Psychology, 2022)
Live stream platforms have transformed the production and consumption of music, allowing KPop music to expand globally. Successful KPop idols are contrasted with large numbers of retired KPop performers, some of whom live in undesirable conditions. Drawing on the attachment theory, loyalty theory, and parasocial interaction theory, this study focuses on a unique group, comeback KPop performers, to examine how they acquire empathetic attachment and sustained loyalty from audiences through live stream shows, and the antecedents (i.e., sustained attractiveness, nostalgic experience, & parasocial interactions) of these two variables. Answering these questions seems important because comeback KPop performers have to interact with audiences without the financial and marketing support from entertainment agencies. The structural equation modelling of 288 responses from 176 Chinese and 112 Korean KPop audiences confirmed that empathetic attachment and sustained loyalty are positively associated with audience purchase intentions; sustained attractiveness and parasocial interactions function as antecedents of these two factors. The findings shed light on the comeback KPop performers who co-create value with audiences through live stream platforms, with theoretical contributions to the three theories mentioned above and managerial suggestions to KPop entertainment agencies, comeback KPop performers, and managers of live stream platforms.